Development and Validation of a LC/MS/MS Method for the Determination of Duloxetine in Human Plasma and Its Application to Pharmacokinetic Study - D. Chandrapal Reddy; A. T. Bapuji; V. Surayanarayana Rao; V. Himabindu; D. Rama Raju; Syed Syedba; H. L. V. Ravikiran (E-Journal of Chemistry)
A selective, high sensitive and high throughput liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) method has been developed and validated for the chromatographic separation and quantitation of duloxetine in human EDTA plasma using fluoxetine (IS) as an internal standard. Analyte and IS were extracted from human plasma by liquid-liquid extraction using MTBE-n Hexane (80:20).The eluted samples were chromatographed on X-terra RP8 (50 mmx4.6 mm, 5 μm particle size) column by using mixture of 30 mM ammonium formate (pH-5.0±0.05) and acetonitrile as an isocratic mobile phase at a flow rate of 0.40 mL/min and analyzed by mass spectrometer in the multiple reaction monitoring (MRM) using the respective m/z 298.08→154.0 for duloxetine and 310.02→148.07 for IS. The linearity of the response/ concentration curve was established in human plasma over the concentration range 0.100-100.017 ng/mL. The lower detection limit (LOD,S/N>3) was 0.04 ng/mL and the lower limit of quantization (LOQ,S/N>10) was 0.100 ng/mL. This LC-MS/MS method was validated with Intra-batch and Inter-batch precision of 5.21-7.02. The Intra-batch and Inter-batch accuracy was 97.14-103.50 respectively. Recovery of duloxetine in human plasma is 80.31% and ISTD recovery is 81.09%. The main pharmacokinetic parameters were Tmax (hr) = (7.25±1.581), Cmax (ng/mL) (44.594±18.599), AUC0→t, = (984.702±526.502) and AUC0→∞, (1027.147±572.790) respectively.